The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0116145
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Composition in Three Freshwater Reservoirs of Different Alkalinity and Trophic Status

Abstract: In order to investigate the factors controlling the bacterial community composition (BCC) in reservoirs, we sampled three freshwater reservoirs with contrasted physical and chemical characteristics and trophic status. The BCC was analysed by 16S rRNA gene amplicon 454 pyrosequencing. In parallel, a complete dataset of environmental parameters and phytoplankton community composition was also collected. BCC in the analysed reservoirs resembled that of epilimnetic waters of natural freshwater lakes with presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
55
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 89 publications
13
55
2
Order By: Relevance
“…Ziros summer (ZS, oligotrophic) and Pamvotis winter (PW, mesotrophic) samples occupied separate branches of the cluster with PW being the most dissimilar. These results differ from previous studies, which showed mesotrophic waters to exhibit similarities either to oligotrophic or to eutrophic waters [17,18]. The complete differentiation of the bacterial community in mesotrophic PW from the other samples supports the suggestion that extreme water physicochemical conditions, like the low temperatures recorded in this study, can shape communities and select taxa that cope well with harsh environment [59].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Ziros summer (ZS, oligotrophic) and Pamvotis winter (PW, mesotrophic) samples occupied separate branches of the cluster with PW being the most dissimilar. These results differ from previous studies, which showed mesotrophic waters to exhibit similarities either to oligotrophic or to eutrophic waters [17,18]. The complete differentiation of the bacterial community in mesotrophic PW from the other samples supports the suggestion that extreme water physicochemical conditions, like the low temperatures recorded in this study, can shape communities and select taxa that cope well with harsh environment [59].…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, a study in several lakes, rivers and reservoirs in Portugal indicated higher similarities for oligotrophic and mesotrophic water bodies compared to eutrophic/hypereutrophic [17]. However, a different pattern was revealed in reservoirs in Belgium where mesotrophic and eutrophic water bodies exhibited more similarities in respect to an oligotrophic reservoir [18]. A core bacterioplankton community was found across an oligotrophic to urban-eutrophic gradient in Lake Michigan [19].…”
Section: Introductionmentioning
confidence: 98%
“…Several other studies have documented that bacterial communities respond to shifts in substrates available within the dissolved organic carbon pool during both freshwater and marine blooms (Lau et al ., ; Teeling et al ., ; Yang et al ., ). Alternatively, pH is known to be a major influence on bacterial community composition in soil (Lauber et al ., ) and freshwater systems (Lindstrom et al ., ; Llirós et al ., ). Therefore, the bloom may have actually influenced the composition of nc‐bacterial communities by changing the lake's pH.…”
Section: Resultsmentioning
confidence: 97%
“…We further tested if patterns in bacterial diversity could explain differences in oxygen consumption. In general, the community data were consistent with expected patterns for oligotrophic freshwater sediments with terrestrial inputs, with a dominance of, in decreasing order of abundance, Betaproteobacteria, Alphaproteobacteria, Gammaproteobacteria, Actinobacteria, Deltaproteobacteria, Clostridia, Sphingobacteria, Planctomycetacia, Bacilli and Acidobacteria (Besemer et al ., ; Llirós et al ., ). We initially hypothesised that high oxygen consumption rates would be associated with high bacterial diversity.…”
Section: Discussionmentioning
confidence: 97%